Between Lynn White and Big Gods – religious sources of pro-environmental attitudes – cross-cultural test of Lynn White's Hypothesis - Adrian Dominik Wojcik (Current Research in Ecological and Social Psychology, 2023)
This study examines the connection between religious beliefs and pro-environmental attitudes using data from three waves of the World Values Survey (WVS) conducted in 1989, 1999, and 2009. The findings reveal a paradoxical relationship between religion and environmental attitudes. While respondents who identified with a specific religious denomination tended to have lower pro-environmental attitudes than those without a religious affiliation, individuals who placed high personal importance on their religiosity and participated in religious practices were more likely to have pro-environmental attitudes. This relationship was moderated by the religious denomination. However, the effects were minimal, explaining only 0.4% of the variance, and were only detected due to the analysis's high statistical power.